Gas Chromatography Results Interpretation: Absolute Amounts Versus Relative Percentages - Hon, G.M.; Abel, S.; Smuts, C.M.; Jaarsveld, P. van; Hassan, M.S.; Rensburg, S.J. van; Erasmus, R.T.; Matsha, T. (IntechOpen, 2012)
None